Impact of the homogeneous junction breakdown in IBC solar cells on the passivation quality of Al2O3 and SiO2: degradation and regeneration behavior. (September 2017) - Müller, Ralph; Reichel, Christian; Yang, Xinbo; Richter, Armin; Benick, Jan; Hermle, Martin
Abstract: Within the last years, many different approaches for the simplified fabrication of interdigitated back-contact (IBC) solar cells have been developed. Most of those concepts result in emitter and back-surface field (BSF) regions that are in direct contact to each other which leads to a controlled breakdown under reverse bias at the p + n + junction. In this work, the influence of the reverse breakdown on the passivation quality of Al2 O3 and SiO2 at the p + n + junction is investigated, not only shedding light on the degradation but also on the regeneration behavior of the cells. It was found that cells with Al2 O3 passivation on the back side degrade during reverse breakdown whereas sister cells with SiO2 passivation were rather unaffected. Consequently, the degradation seems to be related to the passivation layer. However, it is shown that the passivation can be regenerated even under normal operation condition. A possible explanation is the discharging of interface traps, which are getting recharged already at room temperature.